Loss of Cdkn1a protects against MASLD alone or with alcohol intake by preserving lipid homeostasis - Arantza Lamas-Paz; Alejandro Hionides-Gutiérrez; Feifei Guo; Gonzalo Jorquera; Laura Morán-Blanco; Raquel Benedé-Ubieto; Mariana Mesquita; Olga Estévez-Vázquez; Kang Zheng; Marina Mazariegos; Elena Vázquez-Ogando; Elena Blázquez-López; et al. (JHEP Reports)
Background & Aims: Expression of P21, encoded by the CDKN1A gene, has been associated with fibrosis progression in steatotic liver disease (SLD); however, the underlying mechanisms remain unknown. In the present study, we investigated the function of CDKN1A in SLD. Methods: CDKN1A expression levels were evaluated in different patient cohorts with SLD, fibrosis, and advanced chronic liver disease (ACLD). Cdkn1a-/- and Cdkn1a+/+ mice were fed with either a Western diet (WD), a Lieber-DeCarli (LdC) diet plus multiple EtOH (ethanol) binges, or a DuAL diet (metabolic dysfunction-associated fatty liver disease and alcohol-related liver). Primary hepatocytes were isolated and functional assays performed. Results: A significant increase in CDKN1A expression was observed in patients with steatohepatitis and fibrosis (with a positive correlation with both NAFLD Activity Score and fibrosis staging scores), cirrhosis and ACLD. Cdkn1a+/+ mice, fed a DuAL diet exhibited liver injury and cell death increased reactive oxygen species (ROS), and markers of senescence (γH2AX, β-GAL, Cdkn1a/p53) contributing to steatosis and inflammation. In contrast, Cdkn1a-/- mutant mice showed a significant decrease in senescence-associated markers as well as in markers of liver injury, hepatic steatosis and an increase in fatty acid oxidation and reduction in free fatty acid uptake as well as de novo lipogenesis. Mechanistically, activation of the AMPK-SIRT3 was observed in Cdkn1a-deleted animals. Conclusions: Cdkn1a deletion protected against preclinical SLD by promoting fatty acid oxidation and preventing free fatty acid uptake and de novo lipogenesis via the AMPK-SIRT3 axis. CDKN1A expression was found to be directly correlated with increased severity of NAFLD Activity Score and fibrosis in patients with SLD. CDKN1A could be a potential theragnostic target for the treatment of metabolic dysregulation in patients with SLD, with and without alcohol consumption. Impact and implications:: Expression of p21, encoded by the CDKN1A gene, has been associated with fibrosis progression in steatotic liver disease (SLD), but the molecular mechanisms remain elusive. Interestingly, in this study we found that Cdkn1a deletion protected against preclinical SLD by promoting fatty acid oxidation and preventing free fatty acid uptake and de novo lipogenesis, via the AMPK-SIRT3 axis. Translationally, Cdkn1a expression was found to be directly correlated with increased severity of NAFLD Activity Score (NAS) and fibrosis in SLD patients, and therefore, CDKN1A might be used potential theragnostic target for the treatment of metabolically induced SLD, with and without alcohol consumption.